If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9a + -4 + a = 0 Reorder the terms: -4 + 9a + a = 0 Combine like terms: 9a + a = 10a -4 + 10a = 0 Solving -4 + 10a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 10a = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 10a = 0 + 4 10a = 0 + 4 Combine like terms: 0 + 4 = 4 10a = 4 Divide each side by '10'. a = 0.4 Simplifying a = 0.4
| [x^2+x][x-6]=0 | | (6x+5)=(8x-37) | | -10=-8n-2n | | x+x-24=352 | | 2log(x+3)=8 | | 7xy+6xy=96 | | C=38.45x+0.50 | | 7u(3u+1)=0 | | 5sin^2(x)+4sin(2x)+6cos^2(4x)=2 | | 2x+x=2x+7 | | 2x+x=2x-7 | | -3x-2-8x=-13 | | 3(4-X)=6+x | | 0.25=logx | | 3(x^2-5)=2x^2+9 | | log2(9/11) | | 4x+x+-6=10 | | 6+3x=-5x-4 | | 7x+8-4x=-4-3x | | x-6-1=-9 | | -5x+7=-4 | | 2(2+v)-5(-2v+7)=17 | | 139=-4x+2(-6x+3) | | 10=-6a+8a | | (12x-29)=(4x+1) | | x+2x=2x+7 | | 4x^2+2(x+3)(x-3)-12=0 | | cosx=-0.8 | | 4x^2+12x+9=36 | | (7x+5)=33 | | y=cos(1.5x) | | X/6-20=23 |